The Influence of Influencer Marketing, Electronic Word-of-Mouth (E-WOM), and E-Service Quality on Purchase Intention Mediated by E-Trust in Food MSMEs in Bogor Raya - Rachmat Gunawan; Chandra Ayu Pramestidewi (Lembaga Publikasi Ilmiah Nusantara, 2026)
This study examines the effects of Influencer Marketing, Electronic Word-of-Mouth (E-WOM), and E-Service Quality on Purchase Intention through the mediating role of E-Trust among consumers of food MSMEs in Greater Bogor, Indonesia. A quantitative explanatory research design was employed using survey data collected from 350 consumers who had purchased food MSME products online within the previous six months. Respondents were selected through purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The results indicate that Influencer Marketing (β = 0.241), E-WOM (β = 0.417), and E-Service Quality (β = 0.293) significantly and positively influence E-Trust, with E-WOM emerging as the strongest predictor. Furthermore, Influencer Marketing (β = 0.128), E-WOM (β = 0.181), E-Service Quality (β = 0.247), and E-Trust (β = 0.462) positively affect Purchase Intention, with E-Trust representing the most influential determinant. The structural model explains 68.4% of the variance in E-Trust and 76.1% of the variance in Purchase Intention. In addition, E-Trust significantly mediates the relationships between Influencer Marketing, E-WOM, E-Service Quality, and Purchase Intention, with the E-WOM–E-Trust pathway exhibiting the strongest indirect effect. These findings contribute to the digital marketing literature by confirming the pivotal role of E-Trust as the underlying psychological mechanism connecting digital marketing strategies with consumers' purchase intention. Practically, food MSMEs should prioritize customer review management, continuously improve digital service quality, and collaborate with credible influencers to strengthen consumer trust and stimulate purchase intention.